Manajemen Pembelajaran Inovatif untuk Mendukung Program MBKM: Pendekatan Praktis dan Teoritis - Husnul, Nisak Ruwah Ibnatur (Jurnal Akuntabilitas Manajemen Pendidikan, 2025)
This research aims to analyze and develop innovative learning management strategies through practical and theoretical approaches that align with the Merdeka Belajar Kampus Merdeka (MBKM) concept at Pamulang University. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and literature reviews. The subjects of this study are lecturers and students involved in the MBKM Program. The data analysis technique used is triangulation. The research findings indicate that the learning management strategy at Pamulang University focuses on collaboration, flexibility, and project-based learning, supported by digital technology and industry partnerships. The main challenges faced include the readiness of technological infrastructure, the adaptation of lecturers and students to self-directed learning, as well as coordination with external partners and the alignment of academic administration. Nevertheless, best practices in the implementation of MBKM, such as industry collaboration, Project-Based Learning, student exchanges, and academic flexibility, have successfully created an innovative and relevant learning ecosystem, supporting students in developing the skills needed in the workforce.